131 ROSETTED GLIONEURONAL TUMOR IN A PEDIATRIC PATIENT. Issue 1 (1st January 2007) - Scavella, A.; Gardner, R.
Abstract : In the pediatric population, rosette-forming glioneuronal tumor is a rare entity. Review of the literature has noted this tumor more in the adult population and older children (age 11 years and above). We present a case of a 2-year-old female patient who came to clinical attention after a 2-month history of variable amounts of emesis noted at nights and early morning associated with headaches but no other neurologic symptoms. Three days prior to presentation, the patient had persistent emesis and newly developed gait disturbance with truncal ataxia. Due to continued worsening of symptoms, she presented to the emergency room and was subsequently admitted. CT scan and magnetic resonance imaging demonstrated a very large mass having a cystic component with calcification in the left cerebal hemisphere. The tumor was subtotally resected after two attempts. Histologically, the glial component of this patient's tumor was astrocytic, with smaller areas of distinct neuronal component that appeared immature. There was increased proliferative activity in the neuronal/immature neurocytic cell component, a feature that has been described in one other published case. Thus, she was felt to have a papillary or rosetting glioneuronal tumor. The biology of these tumors is not clearly delineated, but review of the literature showed that this subset of tumors may have an unfavorable clinical course. In the management of this patient, she was given a total of six cycles of etoposide, ifosfamide, and carboplatin with mesna. The tumor responded initially, but there were signs of tumor progression after four cycles of chemotherapy. She was noted to have fairly good function even with evidence of progression. In addition, she also received brain and spinal radiation. Her disease appeared stable, but 8 months after diagnosis, follow-up magnetic resonance imaging of the brain demonstrated recurrence of disease with widespread disease in the brain with no spinal metastasis. Despite chemotherapy and radiation, patient succumbed to her illness at 9 months from diagnosis.